The metabolic load of stored blood. Implications for major transfusions in infants. Issue 12 (December 1986) - Ratcliffe, J M; Elliott, M J; Wyse, R K; Hunter, S; Alberti, K G
Abstract : Plasma electrolyte, intermediary metabolite, and hormone concentrations were measured in samples of 110 units of citrate phosphate dextrose blood being used for clinical transfusions. The most important changes from the physiological range were in sodium, potassium, glucose, and lactate concentrations. Mean sodium concentrations fell from 170 mmol/l at the beginning of storage to 156 mmol/l at the end and mean potassium concentrations rose from 7 mmol/l to 25 mmol/l. Glucose had a mean concentration of 20 mmol/l at the beginning of storage and had only fallen to 15 mmol/l at the end. Mean lactate concentrations increased from 7 mmol/l at the beginning of storage to 25 mmol/l at the end. Many samples had cortisol, insulin, and growth hormone concentrations within the physiological range. Citrate phosphate dextrose blood contains a large substrate load that changes during storage and that should be taken into account when infants are transfused large volumes of blood. The strong correlation coefficients with duration of storage for sodium, potassium, and lactate (-0.71, 0.91, and 0.90, respectively) indicate that concentrations of these substrates can be predicted within a narrow range if the duration of blood storage is known.